Organizational Cynicism - Dean, James W.; Brandes, Pamela; Dharwadkar, Ravi (Academy of Management Review, 1998)
What is the nature of the extremely negative attitudes expressed by so many employees toward their organizations? To respond to this question, we introduce the concept of organizational cynicism. We review the literature from several disciplines on this concept and suggest that organizational cynicism is an attitude composed of beliefs, affect, and behavioral tendencies toward an organization. Following our review and conceptualization, we derive implications of this concept and propose a research agenda for organizational cynicism.